Targeting ferroptosis with culinary spices: a dietary strategy for neuroprotection via the Nrf2/GPX4 axis - Hong, Wei; Qing, Yingjie; Liu, Jie (Frontiers in Nutrition, 2026)
The incidence of neurodegenerative diseases (NDs) continues to rise worldwide, while conventional pharmacological treatments remain limitations. Consequently, increasing attention has been directed toward to dietary intervention and nutritional supplementation as complementary strategies to prevent these diseases. Ferroptosis (an iron-dependent cell death driven by toxic lipid peroxidation) has become a key therapeutic target within NDs’ complex pathological landscape. Nuclear factor-erythroid 2-related factor 2 (Nrf2) signaling pathway is the core mechanism of neuron’s resistance to ferroptosis, which can regulate the production of the key anti-ferroptosis enzyme glutathione peroxidase 4 (GPX4). Although commonly used culinary spices are well recognized for their flavor and antioxidant effects, their specific functions as natural ferroptosis inhibitors have not been deeply studied. This review systematically evaluates the neuroprotective potential of these dietary components, and introduces in detail how they can reduce iron accumulation, lipid peroxidation, oxidative stress and neuroinflammation by activating Nrf2/GPX4 pathway. By synthesizing the current evidence, we emphasize a prospect: adding bioactive spices into our daily nutrition plan can be a promising, easy-to-obtain and safe method to help us maintain the stability of nervous system and build resistance to NDs.